Bags impregnated with garlic (Allium sativum L.) and parsley (Petroselinum crispum (Mill.) Fuss) essential oils as a new biopesticide tool for Trogoderma granarium Everts, 1898 pest control - Alzahraa Abdelaty ELMADAWY; Ahmed Fayez OMAR; Tamer ISMAIL (Acta Agriculturae Slovenica)
Stored product pests can cause significant damages and great economic problems in stored commodities and grain cereal. Using synthetic pesticides in the storage pest control has adverse effects on human health. In our study, the toxicity of garlic (Allium sativum) and parsley (Petroselinum crispum) essential oils (EOs) impregnating with three types of bags were assessed against Trogoderma granarium Everts, 1898 adults after different exposure intervals. GC-MS analysis of the investigated EOs revealed that the major components of parsley and garlic were 1, 3, 8-p-menthatriene (23.34 %) and di-allyl disulfide (27.9 %), with (1.40 %) alpha-terpinene and (1 %) of di-alyl tetra-sulfide as minor components respectively. Additionally, comparison the toxicity among the treated bags was assessed based on the LC50 values and a persistence efficiency of the tested EOs was carried out by the LC90 values for each bag type. In all bag types, garlic and parsley had mortality by 100 % for clothes, and 80 % for both plastic and paper bags after 7 days of exposure, respectively. After two and five days of garlic treatment, plastic bags were the most effective, but after seven days of exposure paper bags was more effective than the other two types. Finally, cloth bags treated with EOs were the most effective packaging for insect control, indicating that this approach could be considered as an additional tool to the concept of stored product management.